Spiritualitas Ketaatan: Studi Deksriptif tentang Pertumbuhan Iman Anak Pasca Gempa di Desa Aek Raja - Nicolas Sinaga (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study is to describe the spirituality of children aged 8-12 years in Aek Raja Village after the earthquake in 2022. The research method used is qualitative research. The informant determination technique is purposive sampling based on certain criteria that are in accordance with the research topic. The data collection technique for this study is using semi-structured interviews and documentation in the form of images. Based on the results of the research that has been conducted by the author, children in Aek Raja Village are increasingly active in participating in church activities after the natural disaster that occurred several years ago. Then they are more diligent in communicating with God through prayer. In the Christian faith, praying is not a spiritual activity that is done when someone has time to do it. Praying is also not done when someone has important needs or Likewise, children in Aek Raja Village have communicated with God the Creator through prayer. Children also believe in God. Likewise, children in Aek Raja Village, that they should be children of God always believe in God through the faith they have. Then children have love for others. Love for God is manifested through total obedience to His commandments and living according to His will written in the Word. This love for God becomes a solid foundation for love for others and love for oneself. Love is the essence of God, the nature of God, and the attributes of God. God has given His love to humans, therefore, humans are also expected to give love to Him and love one another. This is because only through mutual love between humans, love for God can be reflected well in human life. Likewise, the children in the village of Aek Raja that children already love others, especially their parents.